About the competence-based technology for educational environment survey - Dmitriy N. Bezgodov (Высшее образование в России)
The article describes the competence-based technology used at Ukhta State Technical University for the estimation of the efficiency of extracurricular activities. This technology includes special matrix and “value-and-competence parallelepiped” designed as the instruments of university educational environment control and correction.